PELAKSANAAN GOOD GOVERNANCE DALAM KERJASAMA PADA KOMISI PELAYANAN PUBLIK PROVINSI JAWA TIMUR DI KOTA SURABAYA - Anindyo Hanugrah Octavian (Faculty of Social and Political Science, 2016)
The Research aims to understand how have program good governance on cooperation on commission public service the province of east java the cooperation between commission public service east java in the city surabaya by radio, television, legal aid institutions and ngos of the society in creating good governance ).The kind of research descriptive, namely is research intended to described and analyze.The locus the study is done in commission public service the province of east java, surabaya.The east ngagel no. 56, surabaya. The result of this research the implementation of the good governance in cooperation between commission public service by a community complaint post , represented the radio , television , legal aid institutions and ngos in indicators information , data , consultation , negotiation , presenting , reported , and in the aspect of mutually beneficial and develop between the two sides are engaged , are already done enough for kpp in support the kpp so far .This is proven would know the community in the existence of kpp and a community complaint post in helping people who have trouble administration . But cooperation do kpp and a community complaint post still it has not optimal, this can be seen as follows: (1) dialogue, interactive done kpp with a community complaint post represented the radio and television perceived less than optimal, because hampered by intensity, caused budget problems. (2) compensation, kpp had difficulty budget, which will the budget affect operational activities done by a community complaint post.Compensation to a community complaint post already provided, troubled about abuse authority. (3) efficiency , in budget cuts done kpp to a community complaint post , influence on the the socialization a community complaint post represented the television .This is evidenced in budget cuts which was previously rp .3.000.000 , – earned the right siar six times live telecast , and when budget cuts to rp .2.000.000 , -just earned the right siar socialization live twice telecast .( 4 ) the effectiveness of , complaints about the problem , is still being felt by less .Because target of kpp in one year the period cooperation with a community complaint post across the province of east java wanted reach of 864 complaints , this troubled about suply given a community complaint post .